1997
DOI: 10.1021/js960221w
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Mechanism of Diclofenac Sodium from Wax Matrix Granules

Abstract: Dissolution behavior of diclofenac sodium (DS) from wax matrix granules (WMGs) prepared using a twin-screw compounding extruder is closely related to swelling ability and solubility of the rate-controlling agent employed. A swellable and soluble (hydroxypropyl)-cellulose (HPC-SL) generates both an expansion of pores inside WMGs and a structural change observed as cracking on the surface of WMGs. These changes are confirmed by mercury porosimetry. Release of DS was increased with an increase in the amount of HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 13 publications
1
52
0
Order By: Relevance
“…The incorporation of a low melting compound into a low melting point wax may form a eutectic mixture or reduce the melting point of the mixture preventing the formation of a solid dosage form. The production of granules using carnauba wax has been reported (Miyagawa et al, 1996(Miyagawa et al, , 1999Sato et al, 1997). The granules contained diclofenac sodium and could be produced at temperatures less than the reported melting point of the wax material.…”
Section: Carriersmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of a low melting compound into a low melting point wax may form a eutectic mixture or reduce the melting point of the mixture preventing the formation of a solid dosage form. The production of granules using carnauba wax has been reported (Miyagawa et al, 1996(Miyagawa et al, , 1999Sato et al, 1997). The granules contained diclofenac sodium and could be produced at temperatures less than the reported melting point of the wax material.…”
Section: Carriersmentioning
confidence: 99%
“…It has been reported that Explotab ® could be used as a "super-absorbent" in hydroxypropylcellulose hot-melt extruded transdermal films to facilitate moisture uptake in wound care applications (Repka et al, 2000b). A similar approach of drug release modification was applied to wax-containing systems (Miyagawa et al, 1996(Miyagawa et al, , 1999Sato et al, 1997). Hydroxypropylcellulose, Eudragit® L, and sodium chloride were incorporated into diclofenac sodium/carnauba wax matrices.…”
Section: Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Prepared tablets were stored at room temperature in airtight photo film container. The technique for tablet production was followed as mentioned previously [7][8][9]. …”
Section: Preparation Of Sustained Release Tabletmentioning
confidence: 99%
“…In 1996 and 1997, Miyagawa, Sato et al prepared controlled release matrices containing diclofenac as a model drug by hot-melt extrusion (Miyagawa et al, 1996;Miyagawa et al, 1999;Sato et al, 1997). The authors used a twin-screw compounding extruder to prepare wax matrix granules composed of carnauba wax, the model drug, and other rate controlling agents.…”
Section: Granules Pellets and Spheresmentioning
confidence: 99%